Pengaruh Resiliensi Akademik terhadap Depresi pada Siswa Korban Bullying di Lingkungan Sekolah Swasta - Syahputra, Rizki Dharma; Akbar, Zarina; Ariyani, Mira; Maulana, Herdiyan; Deasyanti, Deasyanti (Lentera: Jurnal Ilmiah Kependidikan, 2025)
Academic resilience is the ability to endure and recover from difficulties, and it is a key factor in students' educational success, helping them adapt and continue progressing in their studies. Depression is a mental health disorder characterized by feelings of sadness, pessimism, loneliness, and sometimes has a familial tendency. It is associated with morbidity and mortality, often caused by substance abuse or suicidal tendencies. This explanation highlights that depression is a serious issue that can affect anyone and needs to be addressed with proper care and action. The sample in this study consisted of 118 respondents, who were students from a private school, aged 11-18 years, and had experienced bullying. Data collection in this research used two types of scales: the Indonesian Academic Resilience Scale Development and Validation, using Rasch Models, developed by Ramdani, Hanurawan, Ramli, Lasan, & Afdal in 2021, and the Center for Epidemiologic Studies Depression Scale (CES-D) developed by Radloff, L. S. (1977). The analysis method used in this study was regression analysis to examine the relationships between variables. The results indicated a significant influence of academic resilience on depression, with p = 0.032 < 0.05, meaning it has a 3.2% impact.